2014
DOI: 10.1007/s10653-014-9651-2
|View full text |Cite
|
Sign up to set email alerts
|

Geospatial association between adverse birth outcomes and arsenic in groundwater in New Hampshire, USA

Abstract: Background There is increasing evidence of the role of arsenic in the etiology of adverse human reproductive outcomes. Since drinking water can be a major source of arsenic to pregnant women, the effect of arsenic exposure through drinking water on human birth may be revealed by a geospatial association between arsenic concentration in groundwater and birth problems, particularly in a region where private wells substantially account for water supply, like New Hampshire, US. Methods We calculated town-level r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Previous birth outcomes studies were conducted mostly in areas of unusally high arsenic or lead exposure, among populations that also may have been at increased risk of poor overall health and nutritional status ( Huyck et al 2007 ; Xu et al 2012 ; Zheng et al 2014 ). Few birth outcomes studies have examined associations with low to moderate levels of metal exposures that are consistent with background levels in many U.S. communities ( Fei et al 2013 ; Shi et al 2015 ). Research on environmental lead exposure has demonstrated adverse effects at exposure concentrations much lower than in highly exposed populations ( Xie et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous birth outcomes studies were conducted mostly in areas of unusally high arsenic or lead exposure, among populations that also may have been at increased risk of poor overall health and nutritional status ( Huyck et al 2007 ; Xu et al 2012 ; Zheng et al 2014 ). Few birth outcomes studies have examined associations with low to moderate levels of metal exposures that are consistent with background levels in many U.S. communities ( Fei et al 2013 ; Shi et al 2015 ). Research on environmental lead exposure has demonstrated adverse effects at exposure concentrations much lower than in highly exposed populations ( Xie et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study that investigated the role of air pollutants in birth outcomes has reported statistically significant associations between low birth weight and levels of aluminum (in all trimesters), calcium, nickel, silicon, and zinc (in the third trimester), as well as elemental carbon and titanium (in the first trimester) [ 33 , 34 ]. Shi et al reported preterm birth has a stronger spatial association with groundwater arsenic than term low birth weight in New Hampshire, USA [ 35 ]. Manganese is an essential mineral nutrient that plays an important role in fetal development and in other important aspects of metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with our approach, some investigations depend on geo-spatial or spatiotemporal association analysis to study, such as the relationship between adverse birth outcomes and arsenic in the groundwater [32] and the county potential [35]. These parametric modeling approaches [40,44,46] focus on a few data members, whereas our framework can associate more extensive data types that include more than spatial and temporal data.…”
Section: Discussionmentioning
confidence: 99%
“…For two or three studied objects, the following methods have been applied widely for association analysis. The correlation coefficient is a common criterion for detecting a binary association [32]. Some linear regression models have been applied for two or more facets [33].…”
Section: Association Analysismentioning
confidence: 99%